Unraveling the potential of 3D bioprinted immunomodulatory materials for regulating macrophage polarization: State-of-the-art in bone and associated tissue regeneration - Sayan Deb Dutta; Tejal V. Patil; Keya Ganguly; Aayushi Randhawa; Ki-Taek Lim (Bioactive Materials, 2023)
Macrophage-assisted immunomodulation is an alternative strategy in tissue engineering, wherein the interplay between pro-inflammatory and anti-inflammatory macrophage cells and body cells determines the fate of healing or inflammation. Although several reports have demonstrated that tissue regeneration depends on spatial and temporal regulation of the biophysical or biochemical microenvironment of the biomaterial, the underlying molecular mechanism behind immunomodulation is still under consideration for developing immunomodulatory scaffolds. Currently, most fabricated immunomodulatory platforms reported in the literature show regenerative capabilities of a particular tissue, for example, endogenous tissue (e.g., bone, muscle, heart, kidney, and lungs) or exogenous tissue (e.g., skin and eye). In this review, we briefly introduced the necessity of the 3D immunomodulatory scaffolds and nanomaterials, focusing on material properties and their interaction with macrophages for general readers. This review also provides a comprehensive summary of macrophage origin and taxonomy, their diverse functions, and various signal transduction pathways during biomaterial-macrophage interaction, which is particularly helpful for material scientists and clinicians for developing next-generation immunomodulatory scaffolds. From a clinical standpoint, we briefly discussed the role of 3D biomaterial scaffolds and/or nanomaterial composites for macrophage-assisted tissue engineering with a special focus on bone and associated tissues. Finally, a summary with expert opinion is presented to address the challenges and future necessity of 3D bioprinted immunomodulatory materials for tissue engineering.